Neoliberal Democratic Reforms in Post-Gaddafi Era: Implications for Political Stability in Libya, 2011-2016 (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This study investigates the neoliberal democratic reforms in post-Gaddafi era and its implications for political stability in Libya. Specifically, the study examined the contradictions of the ruling class project of democratization in Libya and their implications for political instability in the post-Gaddafi era. The study found that the democratic project as propagated by the ruling class in post-Gaddafis Libya is an intrinsic feature of modernization, a transition from authoritarian to more open political systems, a process linking economic reform and political liberalization perceived as not expressing an organic unity, but separate and either consecutively or concurrently linked. By viewing political instability as an inevitable pendulum of the cyclical transition from authoritarian to more democratic system, neoliberal democracy in post-Gaddafis Libya legitimizes authoritarianism in so far as it promotes modernization and liberal system of free market economy. The implication of the study is that the adoption of a new economic system, as well as western-style political institutions in post-Gaddafi Libya, relegating the consultation and active participation of the Libyan people undermined the democratic project. The exclusion of Libyans in the democratization process ultimately gave rise to political instability in post-revolution Libya. We therefore, recommended a referendum as a preferred option for Libyans to decide economic and political organization of Libya.